GASTRODIPLOMASI DALAM PRURALINGUALISME: DARI MODIFIKASI KEKUASAAN MENJADI CAKRAWALA ANTARBUDAYA PRANCIS-INDONESIA - Tri Asiati; Dian Adiarti; Erna Wardani (Bajang Institute, 2022)
Pluralingualism is an individual's communicative competence in multilingual situations and does not only involve verbal and non-verbal aspects, but also adaptive and adoptive abilities to cultural conventions. The roots of this linguistic politics guide speakers to be knowledgeable, experienced, sociable, synergize and tolerate culture, as well as to eliminate culture shock in its acquisition. One of the subcultures of language speakers is eating, which sometimes have different values and functions from one culture to another. Within the framework of pluralingualism, eating and food occupies a special level, because it can be an instrument of public diplomacy with the term gastrodiplomacy. Gastrodiplomacy is the art of negotiation by mixing and matching culture, culinary, and the essence of the image of nationalism to make foreign cultures real in other countries through a touch of taste. From this tradition, the concept of French pluralism has succeeded in hegemonizing the world through cultural representations of eating and food that are integrated in communicative competence. However, this practice cannot be separated from the context of power, where at first French was synonymous with colonial language and transformed into the term cultural language. Based on this, the problem of modifying power into an intercultural horizon with culinary delights will be analyzed using netnographic methods, document studies, and observation. Meanwhile, the primary research data are: cross-cultural culinary heritage, gastrodiplomacy and efforts to commercialize French cuisine, as well as communicative implementation of French speakers in the culinary existence of the archipelago. Therefore, the result is a description of the modification of power into an intercultural horizon through taste, as well as a communicative implementation of French speakers in the practice of Indonesian culinary gastrodiplomacy as a form of nation branding.